2012
DOI: 10.1103/physrevlett.109.163001
|View full text |Cite
|
Sign up to set email alerts
|

Space-Time Crystals of Trapped Ions

Abstract: Spontaneous symmetry breaking can lead to the formation of time crystals, as well as spatial crystals. Here we propose a space-time crystal of trapped ions and a method to realize it experimentally by confining ions in a ring-shaped trapping potential with a static magnetic field. The ions spontaneously form a spatial ring crystal due to Coulomb repulsion. This ion crystal can rotate persistently at the lowest quantum energy state in magnetic fields with fractional fluxes. The persistent rotation of trapped io… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
195
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(201 citation statements)
references
References 38 publications
4
195
0
Order By: Relevance
“…Its ubiquity spans from condensed matter and atomic physics to high energy particle physics; indeed, examples of the phenomenon abound in nature: superconductors, Bose-Einstein condensates, (anti)-ferromagnets, any crystal, and Higgs mass generation for fundamental particles. This diversity seems to suggest that almost any symmetry can be broken.Spurred by this notion, and the analogy to spatial crystals, Wilczek proposed the intriguing concept of a "timecrystal"-a state which spontaneously breaks continuous time translation symmetry [3][4][5]. Subsequent work developed more precise definitions of such time translation symmetry breaking (TTSB) [6][7][8] and ultimately led to a proof of the "absence of (equilibrium) quantum time crystals" [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its ubiquity spans from condensed matter and atomic physics to high energy particle physics; indeed, examples of the phenomenon abound in nature: superconductors, Bose-Einstein condensates, (anti)-ferromagnets, any crystal, and Higgs mass generation for fundamental particles. This diversity seems to suggest that almost any symmetry can be broken.Spurred by this notion, and the analogy to spatial crystals, Wilczek proposed the intriguing concept of a "timecrystal"-a state which spontaneously breaks continuous time translation symmetry [3][4][5]. Subsequent work developed more precise definitions of such time translation symmetry breaking (TTSB) [6][7][8] and ultimately led to a proof of the "absence of (equilibrium) quantum time crystals" [9].…”
mentioning
confidence: 99%
“…Spurred by this notion, and the analogy to spatial crystals, Wilczek proposed the intriguing concept of a "timecrystal"-a state which spontaneously breaks continuous time translation symmetry [3][4][5]. Subsequent work developed more precise definitions of such time translation symmetry breaking (TTSB) [6][7][8] and ultimately led to a proof of the "absence of (equilibrium) quantum time crystals" [9].…”
mentioning
confidence: 99%
“…1. Two different systems have been proposed: a bright soliton formed by attractively interacting particles on an Aharonov-Bohm ring [6] and ions on a ring in the presence of an external magnetic field [7] (see also [8][9][10][11][12]). These proposals triggered debate in the literature whether time crystal formation is possible.…”
mentioning
confidence: 99%
“…These proposals triggered debate in the literature whether time crystal formation is possible. It seems that different assumptions can lead to contradictory conclusions [13][14][15][16][17][18][19][20][21][22].…”
mentioning
confidence: 99%
“…Tongcang Li et al [4] have suggested a method for actually creating such space-time crystals, by confining ions in a ring-shaped trapping potential with a static magnetic field. They propose that the resultant ion crystal will rotate persistently, with no loss of energy.…”
Section: Testing the Theorymentioning
confidence: 99%